1995
DOI: 10.1597/1545-1569(1995)032<0020:cmfscs>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cranio-Orbito-Zygomatic Measurements from Standard CT Scans in Unoperated Treacher Collins Syndrome Patients: Comparison with Normal Controls

Abstract: Fourteen reproducible cranio-orbito-zygomatic measurements taken from 26 standard axial computed tomographic (CT) scans of unoperated individuals with symmetric forms of Treacher Collins syndrome (TCS) were compared to age-matched controls. The interorbital measurements of the TCS patients were at the mean when compared to their cohort group (medial and lateral orbital wall separation), while the zygomatic measurements were significantly less than normal confirming the extent of malar hypoplasia. The congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…With minimum differences (measuring error below 5%) in direct measurements of osseous structures of the skull and indirect measurements performed on CT scans of the same skulls, they demonstrated that measurements performed on CT scans are highly reliable 11 . According to Posnick et al 17 reported in females in the present study is slightly lower than 80.54±7.20 reported in females 11 . The difference between the findings in this study and previous study 11 may not be unconnected with the difference in race as well as age range difference among study participants.…”
Section: Discussioncontrasting
confidence: 70%
“…With minimum differences (measuring error below 5%) in direct measurements of osseous structures of the skull and indirect measurements performed on CT scans of the same skulls, they demonstrated that measurements performed on CT scans are highly reliable 11 . According to Posnick et al 17 reported in females in the present study is slightly lower than 80.54±7.20 reported in females 11 . The difference between the findings in this study and previous study 11 may not be unconnected with the difference in race as well as age range difference among study participants.…”
Section: Discussioncontrasting
confidence: 70%
“…Other authors have also suffered from groups of patients not truly representative of the TreacherCollins syndrome population and low sample sizes because of the rarity of the condition. 1,17,21 We have shown that geometric morphometrics still has a role in the severely affected child with absent zygomatic arches or complete absence of the orbitozygomatic region. If there is unilateral absence of the orbitozygomatic region secondary to trauma or malignancy, surgeons have used the contralateral normal facial skeleton to design a size-matched zygoma or absent temporomandibular joint process.…”
Section: Discussionmentioning
confidence: 92%
“…The sphenoethmoidal region is positioned posteriorly, closer than normal to the sella, and the cranial base is significantly misshapen (Grayson et al, 1985). Additionally, Frankfurt plane could not be used as a reference in this study due to severe deformities observed in the orbital cavity (Marsh et al, 1986;Posnick et al, 1995). No cranial base differences were observed between TCS and PRS.…”
Section: Discussionmentioning
confidence: 99%